A review of chatter suppression in thin-wall milling: strategies, mechanisms, and applications - Yuwen Sun; Shichao Yan; Shuoxue Sun; Jinbo Niu; Jinting Xu; Mansen Chen; Jun Liu; Dongming Guo (International Journal of Extreme Manufacturing)
Thin-walled parts have been widely employed as critical components in high-performance equipment due to the high specific strength and light weight. However, owing to their relatively weak rigidity and poor damping properties, chatter vibration is likely to occur during the milling process, which severely deteriorates surface quality and decreases machining productivity. Therefore, chatter suppression is essential for improving the dynamic machinability of thin-walled structures and has attracted extensive attention over the past few decades. This paper reviews the current state of the art in research concerning chatter suppression during the milling of thin-walled workpieces. In consideration of the dynamic characteristics of this process, the challenges in design and application of chatter attenuation methods are highlighted. Moreover, various chatter suppression techniques, involving passive, active, and semi-active methods, are comprehensively discussed in terms of basic concepts, working mechanism, optimal design, and application. Finally, future research opportunities in chatter mitigation technology for thin-wall milling are recommended.